The Meaning Of American Slang Lyrics On The Weeknd’s Album The Highlights (Deluxe) - Mentari, Mentari; Asyrafunnisa, Asyrafunnisa; Abeng, Andi Tenri (Fakultas Sastra, Universitas Bosowa, 2024)
Slang is an informal language that developed over time. Sociolinguistics is the study of language in society, how it changes, the kinds of language that exist, and how language affects society. It implied that a society's social life could be influenced by language when social phenomena were present. This study aims to identify the types of slang words and the meanings included in The Weeknd's 36 songs album The Highlights (Deluxe). A descriptive qualitative method was employed to ascertain or to determine the meaning of the slang words and used George Yule's theory of types of word formation to identify the types of slang words. According to the study's findings, The Weeknd used a variety of word structures in his songs in the album. There were 150 pieces of data total from The Weeknd's 27 tracks and was separated into 5 types based on The Weeknd's song lyrics; Clipping, Blending, Coinage, Acoymns, and Compounding. The Weeknd used a lot of slang terms in his songs. The writer discovered that the context of slang words affects their meaning. Many slang words may have offensive or impolite connotations, and some have been determined to have sensitive meanings.